2011
DOI: 10.1002/jcp.22555
|View full text |Cite
|
Sign up to set email alerts
|

Resistin induces monocyte–endothelial cell adhesion by increasing ICAM‐1 and VCAM‐1 expression in endothelial cells via p38MAPK‐dependent pathway

Abstract: Resistin, firstly reported as an adipocyte-specific hormone, is suggested to be an important link between obesity and diabetes. Recent studies have suggested an association between resistin and atherogenic processes. The adhesion of circulating monocytes to endothelial cells is a critical step in the early stages of atherosclerosis. The purpose of the present study was to investigate the effect of resistin on the adhesion of THP-1 monocytes to human umbilical vein endothelial cells (HUVECs) and the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 28 publications
(36 reference statements)
0
65
0
4
Order By: Relevance
“…While adipose tissue constitutes the main source of resistin in mice, this molecule is secreted mainly by monocytes and macrophages in humans (217). Human resistin is implicated in the pathogenesis of atherosclerosis by promoting smooth muscle cell proliferation and migration, ICAM-1 and VCAM-1 expression, as well as via regulating patterns of adhesion and inflammation in atherosclerotic plaques (218, 219). Several colorectal cancer studies have shown a positive correlation between resistin and tumor size based on T-staging and tumor grading (172, 220).…”
Section: Pathophysiological Mechanisms Relating Visceral Adipose Tissmentioning
confidence: 99%
“…While adipose tissue constitutes the main source of resistin in mice, this molecule is secreted mainly by monocytes and macrophages in humans (217). Human resistin is implicated in the pathogenesis of atherosclerosis by promoting smooth muscle cell proliferation and migration, ICAM-1 and VCAM-1 expression, as well as via regulating patterns of adhesion and inflammation in atherosclerotic plaques (218, 219). Several colorectal cancer studies have shown a positive correlation between resistin and tumor size based on T-staging and tumor grading (172, 220).…”
Section: Pathophysiological Mechanisms Relating Visceral Adipose Tissmentioning
confidence: 99%
“…Human recombinant resistin increased the expression of pro-atherogenic molecule, ET-1, VCAM-1 and MCP-1 and down-regulated anti-atherogenic molecule TRAF-3, an inhibitor of CD40 ligand signaling in endothelial cells (Verma et al, 2003). Human resistin was shown to induce adhesion molecule, ICAM-1 and VCAM-1 in endothelial cell and thereby increase monocyte-endothelial cell adhesion (Kawanami et al, 2004;Cho et al, 2011;Hsu et al, 2011). Resistin was expressed by rat vascular smooth muscle cells and it was stimulated by hypoxia or cyclic mechanical stretch (Hung et al, 2008;Wang et al, 2010).…”
Section: Human Resistin In Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%
“…Several environmental chemicals have been reported to be potential activators for ICAM-1 [19][20][21]. Studies have shown that stimuli-induced upregulation of ICAM-1 in endothelial cells was mediated by the activation of MAPK [16]. However, there is little information on the effect of DEHP on ICAM-1 activity in HUVECs.…”
Section: Introductionmentioning
confidence: 96%
“…However, the effect of higher concentrations of DEHP (1-25 μM) on the IL-8 expression in HUVECs remains unknown. ICAM-1, an inducible cell transmembrane glycoprotein of the immunoglobulin supergene family, acts as a key component in inflammatory response for recruitment of leukocytes to the sites of inflammation and is implicated in the pathogenesis of numerous inflammatory diseases such as asthma, rheumatoid arthritis, and atherosclerosis [14][15][16][17][18]. Several environmental chemicals have been reported to be potential activators for ICAM-1 [19][20][21].…”
Section: Introductionmentioning
confidence: 99%